Strengthening the Character of the Sebagasi Chips Center Area as a Tourist Destination: (Case Study: Pagar Alam Road Corridor, Bandar Lampung ) - Herry Maulana Nasution; Citra Persada; M. Irfan Affandi (Pusat Riset dan Inovasi Nasional, 2024)
The development of the chips center area as a tourist destination does not merely rely on the existence of diverse chips products. Other factors also need to be considered, one of which is the visual character of the region. Character strengthening refers to the ability of an area to be understood, interpreted, and dinvigation easily by visitors. In the context of tourist destinations, character strengthening has an important role in attracting tourists and ensuring a pleasant tourist experience. The famous chips center area in Bandar Lampung City is in the corridor of Jalan Pagar Alam. This chip center area has the potential to become an attractive culinary destination for both local and foreign tourists who are projected to become triggers as economic growth in the local area through culinary tourism and shopping tourism. The research method used is SWOT and Appreciative Inquary (AI) by mapping the potentials that exist in the Pagar Alam Jalan Chips Center. Data analysis methods use quantitative descriptive and descriptive qualitative. City design elements identified and analysis are: Figure ground, environment, land use, pathways, nodes and landmarks. The five elements of the city design can strengthen the character and image of the area in the Center for Jalan Pagar Alam as a tourist destination if planned and well organized. Development of the Strengthening of the Character of the Center for Chips Center as a tourist destination is carried out with a tourist concept of 4A+I, namely: Attraction (Attraction), Accessibility (Accessibility), Amenitas (Amenities), Ancillary Service and Institutions (Institutions).